Determinasi Pemantapan Masyarakat Dalam Penataan Dana Desa - Sahala Purba; Ivo Maelina Silitonga; Tasya Dearmaria Simbolon (JAS (Jurnal Akuntansi Syariah), 2022)
This research was conducted to examine and analyze whether openness, accountability, and community involvement can affect the strengthening of the community in managing village funds in the Rawang Panca Arga sub-district, Asahan district, North Sumatra province. This research uses a quantitative approach. All village representative bodies in the Rawang Panca Arga sub-district are the population of this research. The research sample used a saturated sample so that 30 respondents were obtained. The data source in this research is primary data in the form of a questionnaire. The data analysis technique was carried out with descriptive statistics, data instrument testing, and hypothesis testing. This research shows that only openness has a positively and significantly effect on community stabilization in village fund management. Accountability and community involvement do not affect strengthening the community in managing village funds. This research can be a reference for strengthening village communities in managing village funds so that the use of village funds is right on target.